Mapping glacial landforms on the Chirripó massif, Costa Rica, based on Google Earth, a digital elevation model, and field observations - Li, Yingkui (2019)
The Chirripó massif in the Cordillera de Talamanca, Costa Rica, is one of a few sites in Central America that preserve evidence of past glaciation. We mapped glacial landforms in this area using Google Earth high-resolution imagery and a 30-m Shuttle Radar Topography Mission (SRTM) digital elevation model (DEM). Prior field observations, field notes, photographs, and landform maps were used to check and refine the delineated landform boundaries. The composited map includes lateral and terminal moraines, tills, glacial valleys, glacial lakes, nunataks, arêtes, and horns. Glacial extents during three proposed stages were mapped in the Valle de las Morrenas, a major north-facing valley on the massif, based on previous reconstructions. The mapped glacial features cover roughly 22.1 km2, representing the minimum extent of the mHornaximum glaciation during the Last Glacial Maximum (LGM). This refined map provides an important dataset to help reconstruct Quaternary climate change in this tropical highland.